Plasmonic Nanobiosensing: from in situ plant monitoring to cancer diagnostics at the point of care. (7th July 2020) - Crawford, Bridget M; Wang, Hsin-Neng; Strobbia, Pietro; Zentella, Rodolfo; Pei, Zhen-Ming; Sun, Tai-ping; Vo-Dinh, Tuan
Abstract: Nucleic acid biosensing technologies have the capability to provide valuable information in applications ranging from medical diagnostics to environmental sensing. The unique properties of plasmonic metallic nanoparticles have been used for sensing purposes and among them, plasmonic sensors based on surface-enhanced Raman scattering (SERS) offer the advantages of sensitive and muliplexed detection owing to the narrow bandwidth of their characteristic Raman spectral features. This paper describes current applications that employ the unique SERS-based inverse molecular sentinel (iMS) nanobiosensors developed in our laboratory. Herein, we demonstrate the use of label-free iMS nanoprobes for detecting specific nucleic acid biomarkers in a wide variety of applications from cancer diagnostics to genetic monitoring for plant biology in renewable biofuel research.